Regulating Ruminative Web Browsing Based on the Counterbalance Modeling Approach - Morita, Junya; Pitakchokchai, Thanakit; Raj, Giri Basanta; Yamamoto, Yusuke; Yuhashi, Hiroyasu; Koguchi, Teppei (Frontiers in Artificial Intelligence, 2022)
Even though the web environment facilitates our daily life, emotional problems caused by its incompatibility with human cognition are becoming increasingly serious. To alleviate negative emotions during web use, we developed a browser extension that presents memorized product images to users, in the form of web advertisements. This system utilizes the cognitive architecture Adaptive Control of Thought-Rational (ACT-R) as a model of human memory and emotion. A heart rate sensor attached to the user modulates the ACT-R model parameters: The emotional states represented by the model are synchronized (following the chameleon effect) or counterbalanced (following the homeostasis regulation) with the physiological state of the user. An experiment demonstrates that the counterbalanced model suppresses negative ruminative web browsing. The authors claim that this approach of utilizing a cognitive model is advantageous in terms of explainability.